Alkali metal-containing halide, electrolyte, battery, and method for producing halide solid electrolyte

By using alkali metal halides in the halide solid electrolyte and heating under high pressure, the problem of insufficient ionic conductivity of the halide solid electrolyte is solved, and the high conductivity and electrochemical stability are improved.

CN119894828APending Publication Date: 2025-04-25SUMITOMO CHEM CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380064589.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-22
Filing Date
2023-09-07
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

There is room for improvement in the ionic conductivity of the halide solid electrolyte.

Method used

By using alkali metal halides, specifically, the compound has a crystal structure belonging to the space group P63mc and performs heating under a pressure of 1 GPa or above, a halide solid electrolyte with excellent ionic conductivity is produced.

Benefits of technology

It achieves a significant improvement in ionic conductivity, improves electrochemical stability, avoids short circuits in the battery, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894828A_ABST
    Figure CN119894828A_ABST
Patent Text Reader

Abstract

A compound containing an alkali metal element, at least one metal element M selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Y, Al, Ga, In, Bi, Sb, Ge, Ti, Zr, Hf, Sn, Nb, Ta, and W, and a halogen element, the compound having a crystal structure belonging to space group P63mc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an alkali metal halide, an electrolyte, a battery and a method for producing a halide solid electrolyte. Background Art

[0002] In recent years, solid electrolytes have attracted attention as electrolytes used in electrochemical devices such as lithium-ion batteries (Patent Documents 1 to 3). Solid electrolytes are superior to conventional electrolytes in high temperature durability and high voltage resistance, and are therefore considered useful for improving battery performance such as safety, high capacity, rapid charge and discharge, and battery pack energy density.

[0003] As described in Patent Documents 1 to 3, as materials used in solid electrolytes of lithium-ion batteries, solid electrolytes containing halides of lithium and metal elements other than lithium are known. Halide solid electrolytes have advantages that oxide-based or sulfide-based solid electrolytes do not have: they are highly flexible and therefore do not require sintering; they are highly safe because they do not release harmful substances such as H2S, etc.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2020137026

[0007] Patent Document 2: International Publication No. 2022032311

[0008] Patent Document 3: International Publication No. 2021234416 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, there is room for improvement in the ionic conductivity of halide solid electrolytes.

[0011] The present disclosure has been made in view of the above circumstances, and an object of the present disclosure is to provide a method for producing an alkali metal halide and a halide solid electrolyte having excellent ion conductivity, and an electrolyte and a battery including the same.

[0012] Means for solving problems

[0013] The present disclosure includes the following embodiments [1] to

[10] .

[0014] [1] A compound comprising an alkali metal element, at least one metal element M selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Y, Al, Ga, In, Bi, Sb, Ge, Ti, Zr, Hf, Sn, Nb, Ta and W, and a halogen element, wherein the compound has a crystal structure belonging to space group P63mc.

[0015] [2] The compound according to [2], wherein the halogen element includes Cl.

[0016] [3] The compound according to [1] or [2], wherein the metal element includes a trivalent metal element.

[0017] [4] The compound according to any one of [1] to [3], which is represented by the following composition formula (1).

[0018] A α M β X γ (1)

[0019] (Wherein, A is an alkali metal element, X is a halogen element, 1≤α≤4, 0.5≤β≤2, 4≤γ≤8.)

[0020] [5] The compound according to any one of [1] to [4], wherein the metal element M contains at least one element selected from the group consisting of Al, Ga, In, Sc, La and Y.

[0021] [6] The compound according to any one of [1] to [5], wherein the metal element M contains two or more metal elements.

[0022] [7] The compound according to any one of [1] to [6], wherein the halogen element includes two or more halogen elements.

[0023] [8] An electrolyte comprising the compound according to any one of [1] to [7].

[0024] [9] A battery comprising the electrolyte of [8].

[0025]

[10] A method for producing a halide solid electrolyte, comprising the step of heating a raw material at a pressure of 1 GPa or higher.

[0026] Effects of the Invention

[0027] According to the present disclosure, it is possible to provide a method for producing an alkali metal halide-containing and halide solid electrolyte having excellent ion conductivity, and an electrolyte and a battery including the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a diagram showing the results of single crystal X-ray diffraction measurement of the sample of Example 1 corresponding to the c-axis direction (001 direction).

[0029] Figure 2 These are powder X-ray diffraction patterns of the samples of Examples 1 to 4.

[0030] Figure 3 These are the powder X-ray diffraction patterns of the three crystal polymorphs of Li3ScCl6.

[0031] Figure 4 It is a ball-and-stick and polyhedron representation of the structure of γ-Li3ScCl6.

[0032] Figure 5 It is the Cole-Cole plot of the ionic conductivity of Example 3.

[0033] Figure 6 This is a graph showing the results of a charge and discharge test performed on Example 1 at 0.1C.

[0034] Figure 7 This is a graph showing the results of a charge and discharge test performed on Example 1 at 0.2C.

[0035] Figure 8 It is a graph showing the cycle number and discharge capacity for Example 1 and α-Li3ScCl6. DETAILED DESCRIPTION

[0036] The compound of the present embodiment contains an alkali metal element, at least one metal element M selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Y, Al, Ga, In, Bi, Sb, Ge, Ti, Zr, Hf, Sn, Nb, Ta and W, and a halogen element, and the compound has a crystal structure belonging to the space group P63mc. It should be noted that, hereinafter, the compound of the present embodiment is also referred to as an alkali metal halide. Such a compound has excellent ionic conductivity. Therefore, it can be used as an ion conductive material containing an alkali metal halide of the present embodiment.

[0037] The crystal structure can be identified by X-ray diffraction measurement, and in particular, by Rietveld analysis.

[0038] In addition, the electrochemical stability of the halide solid electrolyte has room for improvement. For example, when used as a solid electrolyte, if a sulfide separation membrane is not configured between the negative electrode and the electrolyte, a short circuit may occur in the battery. The alkali metal halide of this embodiment also tends to have excellent electrochemical stability.

[0039] The alkali metal element contained in the alkali metal halide of the present embodiment may be any one of Li, Na, K, Rb and Cs, but may include at least one of Li, Na and K, may include at least one of Li and Na, and may include Li.

[0040] Among the alkali metal elements contained in the alkali metal halide, the ratio of one alkali metal element may be 80 mol % or more, 90 mol % or more, or 95 mol % or more. The one alkali metal element may be at least one of Li, Na and K, at least one of Li and Na, or Li.

[0041] The content of the alkali metal element in the alkali metal halide may be 10 to 40 mol %, 15 to 35 mol %, or 20 to 30 mol % relative to the total amount of atoms contained in the alkali metal halide.

[0042] The metal element M may include at least one element selected from the group consisting of La, Y, Ga, In, Sc, Bi, Sb, Ge, Zr, Sn, Nb and Ta, may include at least one element selected from the group consisting of Ga, In, Sc, La, Y, Sb and Bi, may include at least one element selected from the group consisting of Ga, In, Sc and La, and may include Sc.

[0043] The alkali metal halide may contain only one metal element M, but may contain two or more metal elements M. In addition, the alkali metal halide may contain a trivalent metal element M. In the case of containing two or more metal elements M, two or more trivalent metal elements M may be contained, but a trivalent metal element M and a metal element M with a valence other than three (e.g., divalent or tetravalent or above, or tetravalent) may be contained. As divalent metal elements M, Mg, Ca, Sr, Ba and Zn can be listed. As trivalent metal elements M, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Y, Al, Ga, In, Bi and Sb can be listed. As tetravalent metal elements M, Ge, Ti, Zr, Hf and Sn can be listed. As pentavalent metal elements M, Nb, Ta, Sb and Bi can be listed. When the alkali metal halide contains two or more metal elements M, the metal element M may contain Sc and at least one element selected from the group consisting of La, Y, Ga, In, Bi, Sb, Ge, Zr, Sn, Nb and Ta, and may contain Sc and at least one element selected from the group consisting of Ga, Bi, Sb, Ge, Zr, Sn, Nb and Ta.

[0044] The content of trivalent metal elements in the metal element M may be 30 mol% or more, 40 mol% or more, 50 mol% or more, 80 mol% or more, 90 mol% or more, or 95 mol% or more. The content of Sc in the metal element M may be 30 mol% or more, 40 mol% or more, 50 mol% or more, 80 mol% or more, 90 mol% or more, or 95 mol% or more.

[0045] The metal element M may include a trivalent metal element and a metal element other than a trivalent metal element. The metal element other than a trivalent metal element may be a tetravalent metal element or a pentavalent metal element, and may be at least one element selected from the group consisting of Ga, Ge, Sn, Zr, Bi, Nb, and Ta. In the metal element M, the content of the metal element other than a trivalent metal element may be 50 mol% or less, 30 mol% or less, 20 mol% or less, 15 mol% or less, or 10 mol% or less.

[0046] The content of the metal element M in the alkali metal halide may be 5 to 20 mol %, 8 to 15 mol %, or 10 to 15 mol % relative to the total amount of atoms contained in the alkali metal halide.

[0047] The halogen element contained in the alkali metal halide of the present embodiment may be any one of F, Cl, Br and I, but may include at least one of Cl, Br and I, may include at least one of F, Cl and Br, may include at least one of F and Cl, and may include Cl. The alkali metal halide may also include only one halogen element, but may also include two or more halogen elements. In the case where the alkali metal halide includes two or more halogen elements, the alkali metal halide may include at least one of the halogen elements other than Cl and Cl, and may include Cl and F.

[0048] The content of halogen elements in alkali metal halides can be 40 to 80 mol%, 50 to 70 mol%, or 55 to 65 mol% relative to the total amount of atoms contained in the alkali metal halide. The content of Cl in alkali metal halides can be 50 mol% or more, 60 mol% or more, 70 mol% or more, or 80 mol% or more relative to the total amount of halogen elements contained in the alkali metal halide. The content of halogen elements other than Cl in alkali metal halides can be 50 mol% or less, 40 mol% or less, 30 mol% or less, or 20 mol% or less relative to the total amount of halogen elements contained in the alkali metal halide. The content of halogen elements other than Cl in alkali metal halides can be 0.5 mol% or more, 1 to 30 mol%, or 3 to 20% relative to the total amount of halogen elements contained in the alkali metal halide. The content of F in the alkali metal halide can be 50 mol% or less, 40 mol% or less, 30 mol% or less, or 20 mol% or less relative to the total amount of halogen elements contained in the alkali metal halide. The content of F in the alkali metal halide can be 0.5 mol% or more, 1 to 30 mol%, or 3 to 20 mol% relative to the total amount of halogen elements contained in the alkali metal halide.

[0049] The alkali metal halide may be a compound represented by the following composition formula (1).

[0050] A α M β X γ Z δ (1)

[0051] (In the formula, A is an alkali metal element, X is a halogen element, Z is an element other than A, M and X, 1≤α≤4, 0.5≤β≤2, 4≤γ≤8, 0≤δ≤0.5.)

[0052] α may be 1.5 to 3.5, or 2 to 3.2. β may be 0.8 to 1.5, or 1 to 1.5. γ may be 5 to 7, or 5.5 to 6.5. α may be 2.1 to 3.1, or 2.3 to 3.05.

[0053] β may be 0.9 to 1.4, or 0.95 to 1.3.

[0054] γ may be 5.7 to 6.3, or 5.9 to 6.1.

[0055] δ may be 0 to 0.1, 0 to 0.01, 0 to 0.001, or 0.

[0056] The element that can be introduced as Z is not particularly limited, and may be, for example, at least one selected from the group consisting of C, N, P, O, and S, or at least one selected from the group consisting of N, P, and S.

[0057] As a method for producing an alkali metal halide according to the present embodiment, for example, there can be mentioned a method including a step of heating a raw material under a pressure of 1 GPa or more. The heating temperature may be 200° C. or more.

[0058] As the pressure of pressurization, preferably 2 GPa or more, more preferably 4 GPa or more. In addition, preferably 15 GPa or less, preferably 10 GPa or less. The upper limit and the lower limit can be combined arbitrarily. By controlling to this pressure range, it becomes easy to stabilize the structure containing the alkali metal halide.

[0059] The heating temperature is more preferably 250° C. or higher. The heating temperature is preferably 1500° C. or lower, and more preferably 1300° C. or lower. By controlling the temperature within this range, it becomes easy to stabilize the structure containing the alkali metal halide of the present embodiment.

[0060] The heating rate can be 5°C / min to 200°C / min, 10°C / min to 150°C / min, 20°C / min to 100°C / min, or 30°C / min to 80°C / min. The time required from the atmosphere temperature (e.g., 25°C) to reach the target heating temperature can be 0.1 to 45 minutes, 1 to 30 minutes, 5 to 25 minutes, or 10 to 20 minutes.

[0061] The cooling rate may be 50°C / min to 500°C / min, 80°C / min to 400°C / min, 100°C / min to 300°C / min, or 150°C / min to 250°C / min. The time required from the heating temperature to reaching the atmosphere temperature (e.g., 25°C) may be 0.1 to 20 minutes, 0.5 to 15 minutes, 1 to 10 minutes, or 2 to 8 minutes.

[0062] The holding time at the heating temperature may be 0.1 to 10 hours, 0.5 to 7 hours, or 1 to 5 hours.

[0063] Alternatively, the pressure may be applied until a predetermined pressure is reached and then heating may be performed. Alternatively, the temperature may be lowered and the pressure may be reduced after reaching a predetermined temperature.

[0064] Examples of the raw material include halides of alkali metals and halides of metal elements M.

[0065] The alkali metal halide of the present embodiment can be used as a material for electrochemical devices such as capacitors and batteries. As such a material, for example, an electrolyte (solid electrolyte) material can be cited. As a battery, a lithium ion battery, a sodium ion battery, etc. can be cited as a battery that charges and discharges by moving alkali metal ions between the positive electrode and the negative electrode. In addition, the alkali metal halide of the present embodiment can be used as an electrode material and can be included in at least one of the positive electrode and the negative electrode.

[0066] Hereinafter, the battery of this embodiment is described by taking a lithium ion battery as an example. The lithium ion battery includes a positive electrode and a negative electrode and an electrolyte (solid electrolyte) disposed between the positive electrode and the negative electrode. The alkali metal halide (in this case, a lithium halide) of this embodiment can be included in the electrolyte of the lithium ion battery.

[0067] The positive electrode of the lithium ion battery is not particularly limited, and may be a positive electrode containing a positive electrode active material and, if necessary, a conductive auxiliary agent, a binder, and the like.

[0068] The positive electrode may be a positive electrode having a layer containing these materials formed on a current collector. Examples of positive electrode active materials include lithium (Li) and at least one transition metal selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, and Cu. Examples of such lithium composite metal oxides include LiCoO2, LiNiO2, LiMn2O4, Li2MnO3, LiNi x Mn y Co 1-x-y O2[0 <x+y<1])、LiNi x Co y Al1-x-y O2[0 <x+y<1])、LiCr 0.5 Mn 0.5 O2, LiFePO4, Li2FeP2O7, LiMnPO4, LiFeBO3, Li3V2(PO4)3, Li2CuO2, Li2FeSiO4, Li2MnSiO4, etc.

[0069] The negative electrode of the lithium ion battery is not particularly limited, and may be a negative electrode containing a negative electrode active material and, if necessary, a conductive auxiliary agent, a binder, etc. Examples thereof include metals such as Li, Si, P, Sn, Si-Mn, Si-Co, Si-Ni, In, Au, and alloys containing these metals, carbon materials such as graphite, and materials in which lithium ions are embedded between the layers of the carbon material.

[0070] The material of the current collector is not particularly limited and may be a single substance or an alloy of a metal such as Cu, Mg, Ti, Fe, Co, Ni, Zn, Al, Ge, In, Au, Pt, Ag, or Pd.

[0071] The solid electrolyte layer may have a plurality of layers. For example, in addition to the solid electrolyte layer containing lithium halide of the present embodiment, a sulfide solid electrolyte layer may be included. The solid electrolyte layer containing lithium halide of the present embodiment may have a sulfide solid electrolyte layer between the negative electrode. However, since the solid electrolyte layer containing lithium halide of the present embodiment has high electrochemical stability, even if it does not contain a sulfide solid electrolyte layer and directly contacts the negative electrode, it is not easy to cause a short circuit in the battery. The sulfide solid electrolyte is not particularly limited, but examples thereof include Li6PS5Cl, Li2S-PS5, Li 10 GeP2S 12 , Li 9.6 P3S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li3PS4, etc.

[0072] Example

[0073] (Example 1: Synthesis of hexagonal Li3ScCl6 (γ-Li3ScCl6))

[0074] In order to synthesize γ-Li3ScCl6, first, stoichiometric amounts of LiCl and ScCl3 are mixed in a glove box in a nitrogen atmosphere. Then, the mixture is pressed together with gold foil as a protective material to form pellets. Typically, the pellets are inserted into a sleeve with a lid of boron nitride (BN) in a homemade gold crucible. Next, the sample and the sleeve are inserted into a graphite tube and sealed in a cube of pyrophyllite for high-pressure reaction. The sample cell is pressed to reach 5GPa in 1 hour, and then heated to 1000°C in 3 hours. After keeping at this temperature for 3 hours, the sample is quenched to room temperature within 5 minutes, and then the pressure is released and set to atmospheric pressure within 2 hours. Thus, lithium-containing chloride (γ-Li3ScCl6) is obtained.

[0075] (Example 1')

[0076] A lithium-containing chloride was produced in the same manner as in Example 1 except that the sample cell was pressed so as to reach 8 GPa within 2 hours and the pressure was released and then returned to atmospheric pressure within 12 hours.

[0077] <Evaluation of Crystal Structure>

[0078] Colorless and transparent plate-like crystals were selected for structure determination. Single crystal X-ray structure determination (XRD) data were obtained using a Bruker Kappa APEX 2CCD diffractometer with MoK monochromatized at 123K. α radiation The distance between the crystal and the detector was adjusted to 50 mm. The data were reduced and integrated using the SAINT program. The structure was established by direct methods using OLEX2 based on F 2 All atoms are optimized by the least squares fit of the full matrix. The final least squares optimization is based on the least squares fit of the full matrix with F0 2 ≥2σ(F0 2 ) 2 Numerical absorption correction was performed using the SADABS program for area detectors. The structures were analyzed using SHEL-XS to determine the atomic coordinates of the metal cations.

[0079] As a representative single crystal X-ray diffraction pattern, Figure 1 2 shows the X-ray diffraction measurement of the sample of Example 1 corresponding to the c-axis direction (001 direction).

[0080] (Examples 2 to 4)

[0081] Except for using LiCl and ScCl 3 in amounts to give the composition shown in Table 2, a lithium-containing chloride was produced in the same manner as in Example 1.

[0082] (Example 5)

[0083] A lithium-containing chloride was produced in the same manner as in Example 1 except that LiCl, ZrCl 4 and ScCl 3 were used in amounts to give the composition shown in Table 2.

[0084] (Example 20)

[0085] A lithium-containing chloride was produced in the same manner as in Example 1 except that LiCl, LiF and ScCl 3 were used in amounts to give the composition shown in Table 2.

[0086] (Comparative Example 1)

[0087] ·ball milling

[0088] In an argon atmosphere having a dew point of -70°C or less (hereinafter referred to as a dry argon atmosphere), 0.3201 g of LiCl and 0.8799 g of ZrCl4 were weighed to prepare raw materials.

[0089] The above raw materials were placed in a 50 ml zirconia container for the planetary ball mill, and 65 g of zirconia balls with a diameter of 4 mm were added. The raw materials were treated by a mechanochemical reaction at 380 rpm for 48 hours to obtain a crude composition of Comparative Example 1. The ball mill was carried out in a mode in which the rotation direction was alternately switched clockwise and counterclockwise, with a 10 minute rotation interval and a 1 minute stop interval. The lithium chloride feed composition was Li2ZrCl6.

[0090] Planetary ball mill: PM400 manufactured by Verder Scientific Co., Ltd.

[0091] ·annealing

[0092] The crude composition of Comparative Example 1 obtained above was heated at 230° C. for 5 hours in an argon atmosphere to obtain the lithium-containing chloride of Comparative Example 1 having a feed composition of Li 2 ZrCl 6 .

[0093] <Powder X-ray Diffraction Measurement>

[0094] The crystal structure of the obtained lithium-containing halide was evaluated by powder X-ray diffraction measurement at 25°C. The results are shown in Table 2. In addition, the diffraction patterns of Examples 1 to 4 are shown in Figure 2 In any of the examples, diffraction peaks belonging to the crystal structure of the space group P63mc were confirmed. The measurement conditions of the powder X-ray diffraction measurement were implemented under the following conditions. In addition, the measurement was performed in a glove box after the sample space was protected with a polyimide tape so that the sample was not directly in contact with the atmosphere.

[0095] Measuring device: SmartLab (manufactured by Rigaku Co., Ltd.)

[0096] X-ray generator: CuKα ray source voltage 40kV, current 50mA

[0097] X-ray detector: semiconductor detector

[0098] Measurement range: Diffraction angle 2θ = 5° to 80°

[0099] Scanning speed: 2.5° / min

[0100] (Synthesis of α-Li3ScCl6)

[0101] α-Li3ScCl6 was obtained by heating at 650°C for 12 hours in a silica tube sealed with a stoichiometric mixture of LiCl and ScCl3. It should be noted that the heating rate during heating was 2°C / min and the cooling rate was also 2°C / min.

[0102] (Synthesis of β-Li3ScCl6)

[0103] Stoichiometric amounts of LiCl and ScCl3 were mixed. The mixture was pelletized and placed in a quartz tube sealed under vacuum. The sample was obtained by heating at 650°C for 48 hours. It should be noted that the heating rate and cooling rate during heating were implemented at 5°C / min.

[0104] Figure 3 The X-ray diffraction diagrams of three crystal polymorphs of Li3ScCl6 are obtained by performing powder X-ray diffraction measurement on a material obtained by pulverizing a sample in an agate mortar under the same conditions as the above-mentioned powder X-ray diffraction measurement. It is known that there are two crystal polymorphs in Li3ScCl6, namely, the α phase (α-Li3ScCl6) having a monoclinic (space group: C2 / m) crystal structure and the β phase (β-Li3ScCl6) having a cubic (space group: Fd-3m) crystal structure. Figure 3 As shown in , the Li3ScCl6 synthesized as described above has a hexagonal crystal structure (space group: P63mc), and both the α phase and the β phase have different novel crystal structures. The Li3ScCl6 with this novel crystal structure is also called γ-Li3ScCl6. In addition, using the crystal structure data obtained by the above-mentioned single crystal X-ray structure analysis, the wavelength of the CuKα ray is input through the crystal structure analysis software VESTA (Visualization for Electronic and Structural Analysis). The simulation (theoretical calculation) was performed to obtain the diffraction pattern of the γ-phase-Li3ScCl6. The diffraction pattern of the γ-phase-Li3ScCl6 obtained by theoretical calculation (the bottom graph) is quite consistent.

[0105] Table 1 shows the crystal data of γ-Li3ScCl6 and the data of structural optimization obtained by single crystal X-ray diffraction at 123 K. Li3ScCl6-5GPa and Li3ScCl6-8GPa refer to samples obtained at pressures of 5GPa and 8GPa, respectively (ie, Example 1 and Example 1'). Figure 4 It is a ball-and-stick and polyhedron representation of the structure of γ-Li3ScCl6.

[0106] Table 1

[0107]

[0108] <Evaluation of ionic conductivity>

[0109] A press forming die having a frame die, a punch lower portion, and a punch upper portion was prepared. It should be noted that the frame die was formed of insulating polycarbonate. In addition, the punch upper portion and the punch lower portion were both formed of electronically conductive stainless steel and were electrically connected to the terminals of an impedance analyzer (S11260 manufactured by Solatron Analytical Co., Ltd.).

[0110] The ionic conductivity of the lithium halide is measured by the following method using the above-mentioned pressure forming mold. First, in a dry argon atmosphere, the powder of the lithium halide is filled into the lower part of the punch inserted into the hollow part of the frame mold from the vertical bottom. Then, by pressing the upper part of the punch into the hollow part of the frame mold from the top, a pressure of 370MPa is applied to the powder of the lithium halide inside the pressure forming mold. After the pressure is applied, the punch is fixed from the top and bottom with a clamp, and the impedance of the lithium halide is measured by electrochemical impedance spectroscopy using the above-mentioned impedance analyzer while maintaining a certain pressure.

[0111] The impedance measurement results were used to create a Cole-Cole plot. In the Cole-Cole plot, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the halide solid electrolyte material relative to ion conduction. Using this resistance value, the ion conductivity is calculated based on the following mathematical formula (III). The ion conductivity (σ 25℃ ) are shown in Table 2.

[0112] σ=(R SE ×S / t) -1 (III)

[0113] in,

[0114] σ is the ionic conductivity,

[0115] S is the contact area between the lithium halide and the upper part of the punch (equal to the cross-sectional area of ​​the hollow part of the frame mold),

[0116] R SE is the resistance value of the solid electrolyte material in impedance measurement,

[0117] t is the thickness of the lithium-containing halide when pressure is applied.

[0118] Figure 5 It is the Cole-Cole plot of the ionic conductivity of Example 3. Figure 5 The measurement results at 25°C, 40°C, 60°C, 80°C and 100°C are shown in FIG.

[0119] <Production of Secondary Battery>

[0120] In a dry argon atmosphere, 29 parts by mass, 67 parts by mass, and 4 parts by mass of lithium halide and LiNi were weighed respectively. 1 / 3 Mn 1 / 3 Co 1 / 3 O2 and acetylene black are mixed in a mortar to obtain a mixture.

[0121] 100 mg of lithium halide and 15 mg of the above mixture were stacked in order in an insulating cylinder with an inner diameter of 10 mm to obtain a stacked body. A pressure of 370 MPa was applied to the stacked body to form a first electrode (layer of the above mixture) and a solid electrolyte layer (layer of the above lithium halide).

[0122] Next, 60 mg of In foil was placed in contact with the solid electrolyte layer, and further 2 mg of Li foil was placed in contact with the In foil to obtain a laminated body. A pressure of 370 MPa was applied to the laminated body to form a second electrode.

[0123] A current collector made of stainless steel was attached to the first electrode and the second electrode, and then a lead was attached to the current collector. All components were placed in a desiccator and sealed, thereby obtaining a secondary battery.

[0124] <Charge and discharge test>

[0125] The test was carried out using the following product as a charge and discharge tester.

[0126] Charge and discharge tester: Toyosystem Co., Ltd. TOSCAT-3100

[0127] The charge and discharge test was carried out at 60° C. at three C rates of 0.1C, 1C, and 3C.

[0128] Charge at a constant current and constant voltage (CCCV charging) to 3.7 V at a current density corresponding to each C rate.

[0129] For discharging, discharge to 1.9 V at a current density corresponding to each C rate.

[0130] After manufacturing the secondary battery, obtain an open-circuit voltage without short circuit, and determine that the secondary battery for which the charge capacity and discharge capacity have been confirmed in the above charge and discharge tests is capable of charge and discharge.

[0131] In addition, for Example 1, perform charge and discharge tests 5 times at C rates of 0.1C and 0.2C. Figure 6 It is a graph showing the results of the charge and discharge test for Example 1 at 0.1C. Figure 7 It is a graph showing the results of the charge and discharge test for Example 1 at 0.2C. Figure 8 It is a graph showing the cycle number and discharge capacity for Example 1 and α-Li3ScCl6. In Figure 8 it, the discharge capacities obtained by measuring 5 cycles each at C rates of 0.1C, 0.2C, and 0.5C for γ-Li3ScCl6 and the discharge capacity obtained by measuring 10 cycles at 1C are shown. In addition, the discharge capacities obtained by measuring 5 cycles each at C rates of 0.1C and 0.2C for α-Li3ScCl6 are shown.

[0132] Table 2

[0133]

[0134] The lithium-containing chlorides of Examples 1 to 5 and 20 have good ionic conductivity compared to the comparative examples.

[0135] <Calculation of Li ion diffusion behavior and evaluation of calculation results>

[0136] Regarding the Li ion diffusion behavior, based on molecular dynamics simulation, calculate and obtain the mean square displacement of Li in the compound belonging to the space group P63mc.

[0137] Currently, although not wishing to limit the claims of the present application, the diffusion behavior of all Li ions shown in the present application and the mean square displacement obtained as a result thereof are calculated by using the computational chemistry software "Vienna ab initio simulation package (VASP)" provided by the University of Vienna, Austria, which is widely used and known to those skilled in the art.

[0138] Specifically, a supercell with 36 Li, 12 trivalent atoms, and 72 Cl atoms was used to perform molecular dynamics calculations to obtain the mean square displacement of Li. For element substitution structures, element substitution was performed based on the structure by the above method. As calculation conditions, density functional PBE was used, and the nPT ensemble was used to obtain MD calculations with a time step of 1fs, a simulation time of 300ps, and a simulation temperature of 700K. The non-integer occupied number sites of trivalent atoms are selected to occupy / be occupied according to the occupancy rate in the most thermodynamically stable way.

[0139] The mean square displacement of Li ions was determined by the following formula (nn).

[0140] Li ion mean square displacement = (Σ n (r(n, t) - r(n, 0)) 2 ) / N (nn)

[0141] Here, r(n, t) is the coordinate of the nth Li atom at time t, and N is the total number of Li atoms contained in the calculation unit cell.

[0142] [Example 1]

[0143] The mean square displacement of Li in γ-Li3ScCl6 of Example 1 was calculated and determined based on molecular dynamics simulation. The results are shown in Table 3 below.

[0144] [Examples 6 to 11]

[0145] For a compound having the same crystal structure as γ-Li3ScCl6 and in which the Sc element is replaced by a trivalent element, the Li mean square displacement of the compound was calculated and determined based on molecular dynamics simulation. The results are recorded in Table 3 below.

[0146] [Example 12]

[0147] For a compound having the same crystal structure as γ-Li3ScCl6 and in which the site of the Sc element is occupied by two trivalent elements, the Li mean square displacement of the compound is calculated and obtained based on molecular dynamics simulation. It should be noted that, as a reference, an example in which Ga and Sc each occupy 50 mol% of the site is shown, but this does not exclude other compositions. The results are recorded in Table 3 below.

[0148] [Examples 13 to 19]

[0149] For compounds in which one Sc in the supercell of γ-Li3ScCl6 is replaced by a tetravalent or pentavalent element, the Li mean square displacement of the compound is calculated and obtained based on molecular dynamics simulation. In this model, when the Sc atom is replaced by a tetravalent element, as charge compensation, the Li equivalent to the number of atoms replaced is deleted from the closest site. In addition, in the case of replacement with a pentavalent element, as charge compensation, the Li multiple of the number of atoms replaced is deleted from the closest site. It should be noted that, as a limitation of the calculation model, a composition in which Sc is replaced by about 8 mol% is shown, but this does not exclude other compositions. The results obtained are recorded in Table 3 below.

[0150] Table 3

[0151]

[0152] As shown in Table 3 above, each compound of Examples 1 and 6 to 19 showed a number of The mean square displacement of Li ions is much greater than that of This means that Li diffuses in the solid and it is a solid electrolyte that can conduct Li.

Claims

1. A compound comprising: Alkali metal elements, at least one metal element M selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Y, Al, Ga, In, Bi, Sb, Ge, Ti, Zr, Hf, Sn, Nb, Ta and W, and Halogen elements, The compound has a crystal structure assigned to space group P63mc.

2. The compound according to claim 1, wherein The halogen element includes Cl.

3. The compound according to claim 1 or 2, wherein The metal element includes a trivalent metal element.

4. The compound according to claim 1 or 2, which is represented by the following composition formula (1): A α M β X γ (1) Wherein, A is an alkali metal element, X is a halogen element, 1≤α≤4, 0.5≤β≤2, 4≤γ≤8.

5. The compound according to claim 1 or 2, wherein The metal element M includes at least one element selected from the group consisting of Ga, In, Sc, La, Y, Sb, and Bi.

6. The compound according to claim 1 or 2, wherein The metal element M includes two or more metal elements.

7. The compound according to claim 1 or 2, wherein The halogen elements include two or more halogen elements.

8. An electrolyte comprising the compound according to claim 1 or 2.

9. A battery comprising the electrolyte according to claim 8.

10. A method for producing a halide solid electrolyte, comprising the step of heating a raw material at a pressure of 1 GPa or more.

Citation Information

Patent Citations

  • Solid electrolyte material and battery using same

    WO2020137026A1

  • Solid-state conductor materials

    WO2021234416A1

  • Electrolyte material and methods of forming

    WO2022032311A1